Can we measure the structural dimension of social capital with digital footprint data? An assessment of the convergent validity of an indicator extracted from digital footprint data - Michael Weiler; Nora Jansen; Oliver Hinz (Schmalenbach Journal of Business Research (SBUR), 2024)
Network analytical metrics often seek to capture the structural dimension of social capital, but such data collections using traditional social research tools often suffer from biases like interviewer effects and are usually only suitable to study small groups of participants. Digital sources of social relations might offer great potential for facilitating such measures though, because they digitally store unprecedented amounts of relational data, free from the limitations associated with self-reported data. This study therefore compares individual node degrees collected through a~contact diary (i.e., overall-social capital), and a~counterpart extracted from digital footprint data from the social media network, Facebook (i.e., social media network-social capital). The findings suggest that researchers conducting empirical studies involving the concept thus should not ignore social media network-social capital as a~practical alternative measure of overall-social capital; it provides a~sound approximation but only after controlling for other influential factors. In particular, our results highlight that the usability of the digital social capital metric is conditional on the three-way interaction between the variables gender, age, and social media network-social capital. Thus, the evidence from our study, in turn, also intimates that individuals act heterogeneously in the digital sphere with respect to their networking behaviour.
Keywords: 650; Contact diary; Convergent validity; Digital footprint data; Personal network; Social capital; Validation study